Renaissance des études afromexicaines et production de nouvelles identités ethniques - Odile Hoffmann (Journal de la Société des Américanistes)
The renaissance of Afromexican studies and the creation of new ethnic identities. For many years the studies on black populations in Mexico focused mainly on historic themes. During the past few years, studies regarding Mexican black populations have begun to multiply and to diversify towards a more contemporary approach. These studies are responding to a small but real mobilization of some Afro-Mexican groups, which are venturing into the cultural and public arenas, and less frequently into the political realm. The critical revision of the present and past bibliography allows us to pinpoint the challenges and specificities of the Mexican situation. Furthermore, we analyze the strategies of the participants in the current debates, mainly academic, political and cultural activists. Facing a process of rapid and exogenous ethnicization, we are proposing alternative approaches and leads to consider in this field of study.